Ameliorative inhibition of sirtuin 6 by imidazole derivative triggers oxidative stress-mediated apoptosis associated with Nrf2/Keap1 signaling in non-small cell lung cancer cell lines - Dindi, Uma Maheswara Rao; Al-Ghamdi, Sameer; Alrudian, Naif Abdurhman; Dayel, Salman Bin; Abuderman, Abdulwahab Ali; Saad Alqahtani, Mohammed; Bahakim, Nasraddin Othman; Ramesh, Thiyagarajan; Vilwanathan, Ravikumar (Frontiers in Pharmacology, 2024)
Background: Redox homeostasis is the vital regulatory systems with respect to antioxidative response and detoxification. The imbalance of redox homeostasis causes oxidative stress. The nuclear factor-erythroid 2 p45-related factor 2 (Nrf2, also called Nfe2l2)/Kelchlike ECH-associated protein 1 (Keap1) signaling is the major regulator of redox homeostasis. Nrf2/Keap1 signaling is reported to be involved in cancer cell growth and survival. The high level of Nrf2 in cancers is associated with poor prognosis, resistance to therapeutics, and rapid proliferation framing Nrf2 as an interesting target in cancer biology. Sirtuins (SIRT1-7) are class III histone deacetylases with NAD+- dependent deacetylase activity that backs a remarkable impact on antioxidant and redox signaling (ARS) linked with Nrf2 deacetylation there by increasinges its transcription by epigenetic modifications identified as crucial event in cancer progression under the influence of oxidative stress in various transformed cells. SIRT6 plays an important role in the cytoprotective effect of multiple diseases, including cancer. This study was aimed to inhibit SIRT6 by an imidazole derivative Ethyl 2-[5-(4-chlorophenyl)-2-methyl-1-H-Imidazole-4-yl) acetate to assess its impact on Nrf2/Keap1 signalling in A549 and NCI-H460 cell lines. Method: Half maximal inhibitory concentration (IC50) of Ethyl 2-[5-(4-chlorophenyl)-2-methyl-1-H-Imidazole-4-yl) acetate is fixed by cell viability assay. The changes in the gene expression of important regulators involved in this study are conducted by Quantitative Real-time PCR (qRT-PCR) and the its protein expression changes were confirmed by western blotting. The changes in the antioxidant molecules are determined by bBiochemical assays. Further, mMorphological studies were performed to observe the generation of rReactive oxygen species, mitochondrial damage, and apoptosis. Results: We inhibited SIRT6 by Ethyl 2-[5-(4-chlorophenyl)-2-methyl-1-H-Imidazole-4-yl) acetate and demonstrated that SIRT6 inhibition impacts on modulation of on antioxidant and redox signaling. The level of antioxidant enzymes and percentage rReactive oxygen species scavenging activity were depleted. The morphological studies showed ROS generation, mitochondrial damage, nuclear damage, and apoptosis. The molecular examination of apoptotic factors confirms apoptotic cell death. Further, molecular studies confirm the changes in Nrf2 and Keap1 expression during SIRT6 inhibition. Conclusion: The overall study suggests that SIRT6 inhibition by imidazole derivative disrupts Nrf2/Keap1 signalling leading to oxidative stress and apoptosis induction.